EccentriCities : writing in the margins of modernism : St. Petersburg to Rio de Janeiro - Allen, Sharon Lubkemann, 1970- (Durham modern languages series., 2013)
This book critically considers how geo-historically distant and disparate urban sites give rise to peculiarly parallel polyphonic fictional forms. It redefines new constellations (eccentric, concentric, ex-centric) for understanding geo-cultural and generic dimensions of modernist and post-modern literature and theory.